PELATIHAN PEMBUATAN APLIKASI BERBASIS WEB UNTUK PORTOFOLIO SISWA/I MENGGUNAKAN MEDIA WORDPRESS DAN GITHUB - Alwiyah Rachman; Ahmad Nuryadi; Ahkmad Fazmi Septiandi; Bayu Urip Pandiangan; Deni Setia Budi; Muhammad Hafidz Asyauri; Noveindra Salim; Leonard Viffo; Rapli Saputra; Wahyu Wibowo; Galuh Saputri (Abdi Jurnal Publikasi, 2023)
In the current era of technological development, it has greatly affected daily life and organizational life. Many organizations and even everyone has used web-based applications, both in personal projects, and in companies, because they are easily accessed anytime and anywhere by everyone. Therefore, with this theme as a learning media that can later be used after graduation and want to continue to the job level. The partner of this activity is SMK Negeri 43 Jakarta. This material is also brought as a means of training for SMK Negeri 43 in using the Wordpress application, and how to create a Portfolio using Wordpress. The stages of the event from preparation, implementation and evaluation. The preparation stage is a survey to the place asking for permission and submission of proposals. Stages of direct activities in place on Monday, November 06, 2023, then presentation of material. The results of the activity gave students insight and understood that a web-based portfolio would be more flexible. The results of this research in the form of a web-based portfolio will be an important alternative because the web-based portfolio has several advantages, namely more concise and flexible. The media used in making this web-based Student Portfolio uses Wordpress which is the most popular media for creating websites in the form of personal blogs, company sites, education, and even commercials such as online stores. After the application has been made so that it can be accessed